Gaps in Naloxone Ownership among People who Inject Drugs during the Fentanyl Wave of the Opioid Overdose Epidemic in New York City, 2018. Issue 1 (December 2022) - Rivera, Alexis V.; Nolan, Michelle L.; Paone, Denise; Carrillo, Sidney A.; Braunstein, Sarah L.
Background : Community distribution of naloxone, a medication that reverses opioid overdose, is an effective public health strategy to prevent overdose deaths. However, data are limited on who has naloxone during the current fentanyl wave of the opioid overdose epidemic in the United States. We aim to determine correlates of naloxone ownership among a community sample of people who inject drugs (PWID) from New York City (NYC). Methods: Data were drawn from the National HIV Behavioral Surveillance Study among PWID. Participants were recruited via respondent-driven sampling. Eligible participants completed an interviewer-administered survey. Log-linked Poisson regression was used to determine adjusted prevalence ratios (aPR) and 95% confidence intervals (CIs) current naloxone ownership. Results: Of 503 PWID, 60% currently owned naloxone. In the past 12 months, 74% witnessed an opioid overdose and 25% experienced one. Those who experienced current homelessness were less likely to own naloxone (aPR: 0.79; 95% CI: 0.68, 0.91), as were those who had been recently incarcerated (aPR: 0.83; 95% CI: 0.71, 0.97). Respondents who reported recent known or possible fentanyl use were more likely to own naloxone (aPR: 1.23; 95% CI: 1.07, 1.43) as were those who experienced an opioid overdose in the past 12 months (aPR: 1.33; 95% CI: 1.15, 1.53). Conclusions: The prevalence of naloxone ownership among PWID in NYC was high, potentially due to widespread community naloxone distribution programs; however, gaps in naloxone ownership existed. Interventions that further ease access to naloxone, such as reclassifying naloxone as an over-the-counter medication and making it available "off the shelf, " should be considered. More research is needed to identify barriers to access, uptake, and sustained possession within this group to maximize the impact of naloxone distribution during the ongoing fentanyl wave of the opioid overdose epidemic.